2006
DOI: 10.1562/2006-01-12-rn-774
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Reacts with Singlet Oxygen to Produce Hydrogen Peroxide

Abstract: Singlet oxygen is a highly reactive electrophilic species that reacts rapidly with electron-rich moieties, such as the double bonds of lipids, thiols, and ascorbate (AscH-). The reaction of ascorbate with singlet oxygen is rapid (k = 3 × 10 8 M -1 s -1 ). Here we have investigated the stoichiometry of this reaction. Using electrodes to make simultaneous, real-time measurements of oxygen and hydrogen peroxide concentrations, we have investigated the products of this reaction. We have demonstrated that hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 23 publications
4
53
0
Order By: Relevance
“…This situation would quickly lead to the production of other ROS. For example, the reaction of 1 O 2 with the high amount of ascorbate in the chloroplast produces H 2 O 2 under physiologically relevant conditions [37]. This would explain the increased H 2 O 2 observed specifically in HL-exposed BSC chloroplasts [3,4], despite this HL exposure not promoting substantial photoinhibition in the rest of the leaf [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…This situation would quickly lead to the production of other ROS. For example, the reaction of 1 O 2 with the high amount of ascorbate in the chloroplast produces H 2 O 2 under physiologically relevant conditions [37]. This would explain the increased H 2 O 2 observed specifically in HL-exposed BSC chloroplasts [3,4], despite this HL exposure not promoting substantial photoinhibition in the rest of the leaf [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…that H 2 O 2 could be generated by a specific receptor-ligand interaction in cells and in cell-free systems, although the mechanism of this generation was not well defined. Buettner and co-workers (10,23) showed that ascorbate reacts with singlet oxygen to generate H 2 O 2 , and it is conceivable that Lzm-S could react with singlet oxygen to produce a similar reaction. Recently, NADPH oxidase (Nox4) has been identified in the vasculature as a source of ROS that produces H 2 O 2 (30).…”
Section: Discussionmentioning
confidence: 99%
“…In order to measure production of H 2 O 2 , one of the most stable reactive oxygen species and the end product of other ROS enzyme reactions , the ROS‐Glo H 2 O 2 Assay (Promega G8820, Southampton, UK) was carried out. Cells were plated in a 96‐well plate (4000–8000 cells per well for whole population and 100–300 cells per well for selected subpopulations).…”
Section: Methodsmentioning
confidence: 99%